HUBUNGAN KONSUMSI GARAM DAN TEKANAN DARAH PADA WANITA DI DESA BATUR JAWA TENGAH - Rosiana Eva Rayanti; R. L. N. K.Retno Triandhini; Debby Helda Sentia (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Excessive salt consumption is a factor that can contribute to the incidence of hypertension and trigger coronary heart disease and stroke Objective: to determine the level of salt consumption, nutritional status, clinical examination, and the relationship between salt consumption and blood pressure in women in Batur Village Method: Quantitative descriptive with design cross-sectional for 106 women aged 35-55 years. The research instrument is Recall 1x24 hours, Body Mass Index (BMI), Mid-Upper Arm Circumference (MUAC), waist-hip circumference ratio, blood pressure, uric acid test, Blood Sugar Level (BSL) and Fasting Glucose (FG). Results: The average salt consumption of respondents is 4.5 grams’/day shows that it does not exceed the recommended limit of Regulation of Minister of Health No. 30 of 2013 (5 grams/day). The majority of BMI is level 1 obesity (39.6%), MUAC (93%) has a normal category. BMI and Waist-Hip Circumference Ratio (WHCR) (65.1%) has a risk category. Blood pressure with the highest criteria (47% systolic; 35% diastolic) has a pre-hypertensive category. Uric acid level, BSL and FG are normal. There is no significant relationship between salt consumption and systolic blood pressure (p =0.373), and there is a significant relationship between salt consumption and diastolic blood pressure (p = 0.002; r = 0.471) Conclusion: the salt consumption of respondents is normal below the recommended limit, the nutritional status of most respondents has a level 1 obesity category and there is a significant relationship between salt consumption and diastolic blood pressure in women in Batur Village